2016
DOI: 10.1037/pac0000173
|View full text |Cite
|
Sign up to set email alerts
|

Turkish-Dutch youths’ attitude toward violence for defending the in-group: What role does perceived parenting play?

Abstract: This study examines a factor that has thus far received little attention in research on attitudes toward violent in-group defense, namely, the role of perceived parental ethnic socialization. We hypothesized that perceived parental ethnic socialization (i.e., cultural socialization, egalitarianism, bias/mistrust) affects attitudes toward violence in defense of the in-group by others as well as willingness to use such violence oneself via its influence on collective identity factors (in-group connectedness, col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 49 publications
(125 reference statements)
1
21
0
Order By: Relevance
“…Findings, however, were considerably mixed, making it difficult to draw clear conclusions regarding the links between preparation for bias and youth adjustment (see Table ). Among the 69 studies that examined links between preparation for bias and youth adjustment, many reported null associations (e.g., Atkin et al, ; Else‐Quest & Morse, ; Ferrari, Ranieri, Barni, & Rosnati, ; French & Coleman, ; Tran & Lee, ), a few reported both positive and negative effects (e.g., Kyere & Huguley, ), and a few found preparation for bias to be associated with increased risk (e.g., Daga & Raval, ; van Bergen, Ersanilli, Pels, & De Ruyter, ). In terms of risk, some studies found that preparation for bias directly predicted greater maladjustment such as higher depressive symptoms (e.g., Liu & Lau, ; Nelson et al, ), whereas other studies found that it exacerbated the negative effect of stressors on adjustment (e.g., Banerjee, Rowley, & Johnson, ; Dotterer & James, ).…”
Section: Associations Between Family Ethnic–racial Socialization and mentioning
confidence: 99%
“…Findings, however, were considerably mixed, making it difficult to draw clear conclusions regarding the links between preparation for bias and youth adjustment (see Table ). Among the 69 studies that examined links between preparation for bias and youth adjustment, many reported null associations (e.g., Atkin et al, ; Else‐Quest & Morse, ; Ferrari, Ranieri, Barni, & Rosnati, ; French & Coleman, ; Tran & Lee, ), a few reported both positive and negative effects (e.g., Kyere & Huguley, ), and a few found preparation for bias to be associated with increased risk (e.g., Daga & Raval, ; van Bergen, Ersanilli, Pels, & De Ruyter, ). In terms of risk, some studies found that preparation for bias directly predicted greater maladjustment such as higher depressive symptoms (e.g., Liu & Lau, ; Nelson et al, ), whereas other studies found that it exacerbated the negative effect of stressors on adjustment (e.g., Banerjee, Rowley, & Johnson, ; Dotterer & James, ).…”
Section: Associations Between Family Ethnic–racial Socialization and mentioning
confidence: 99%
“…To increase the pool of minority youth, the survey was subsequently dispersed through two websites that function as community platforms with news, forums, and dating services for youth of Moroccan and Turkish descent (see Maroc.nl and Hababam.nl). The introduction of the school survey and digital survey stated, “University researchers want to learn how youth of different backgrounds perceive each other.” For the in-depth interviews, we invited students who were between 16 and 22 years old, who had indicated their willingness to be interviewed, and who had scored either high or low on two or more of the following survey items: engagement in conflicts or fights for ethnic/religious reasons, a favorable attitude toward violence in defense of the in-group, feelings of in-group superiority, and a social distance to out-groups (all important to antagonism, see Doosje, Van den Bos, Loseman, Feddes, & Mann, 2012; Van Bergen et al, 2016). Youth were interviewed in 2012.…”
Section: Methodsmentioning
confidence: 99%
“…The interview focused on five pre-identified topics, although its format offered abundant space for additional emerging themes. The five topics included ethnic and religious identification, views, and behaviors toward out-groups, perceived treatment and/or stigmatization of the in-group, parental in/out-group views, and parental ethnic socialization in relation to the above topics (Doosje et al, 2012; Hughes et al, 2008; Van Bergen et al, 2016). Examples of questions for each topic (Turkish Dutch youth) include, “Do you feel Turkish?” “Is Islam important to you?” “How do you feel about non-Muslims?” “Has it ever happened to you that you felt unfairly treated as a Turk/ Muslim?” “Do you think a person’s ethnic background is relevant?” Once youth had shared their own views and experiences, they were asked to describe their parents’ responses, behavior, and viewpoints in relation to these topics, for instance, by asking the question, “How do your parents feel about this?”…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that, rather than actual deprivation, what matters in particular may be minority-group members' subjective experience of it. Indeed, a recent study conducted with Muslim youth in the Netherlands suggested that perceptions of relative deprivation and consequent violent intentions may stem in parts from intergroup experiences their parents teach them about [39].…”
Section: Relative Deprivation and Collective Actionmentioning
confidence: 99%